2011
DOI: 10.1007/978-3-642-23333-3_13
|View full text |Cite
|
Sign up to set email alerts
|

Reference Framework for E-participation Projects

Abstract: Abstract. Accommodating the various requirements from distinct perspectives in e-participation calls for a holistic engineering approach for e-participation systems analysis and design. This paper presents research results towards a reference framework for e-participation projects. An analysis of procedural models for e-participation and enterprise architectures in the context of e-participation shows that a holistic approach is necessary. A sophisticated and holistic engineering approach for e-participation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 17 publications
1
19
0
10
Order By: Relevance
“…Participation is an important and growing topic for researchers and government practitioners [1][2][3][5][6][7][8][9][10]13,18,21,40,52]. It has gained greater prominence since the advent of the Internet and the move towards e-participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participation is an important and growing topic for researchers and government practitioners [1][2][3][5][6][7][8][9][10]13,18,21,40,52]. It has gained greater prominence since the advent of the Internet and the move towards e-participation.…”
Section: Discussionmentioning
confidence: 99%
“…Since the Internet age, there have been changes in participation channels and processes, using various electronic media for communication and interaction. This is the realm of "digital participation", where government interacts with citizens through the Internet and other ICT [3][4][5][6][7][8][9][10]. Recently, citizen participation is not only through physical and face-to-face activities, but also digital technologies, such as Twitter, Facebook, WhatsApp, e-mail, websites, and mobile applications.…”
Section: Introductionmentioning
confidence: 99%
“…A similar concept corresponding to the particular long-term and high stakes ethos of the PSD domain can be institutionalized under the tentative label of Information. Published discourse on this subject has already identified potential pathways for addressing this need for conceptual rigor, along with examples of implementation in other domains: o Various authors have suggested possible strategies for exploration and standardization of alternative concepts for e-participation that are equally applicable for the PSD context, such as: a master template on how to generate an action plan for establishing participatory decision-making in different contexts with varying requirements (Scherer & Wimmer, 2011); a framework for setting scope (Tambouris, Liotas, Kaliviotis, & Tarabanis, 2007); a model of 'participatory sensing' (Estrin, 2010); and, a sustainabilitybased model for designing participatory processes (Islam, 2008). o An illustrative table of parallel concepts and their evolution in other disciplines is given below ( Table-7).…”
Section: Conclusion and Future Recommendations -The Way Forwardmentioning
confidence: 99%
“…The participatory budgeting offers in German municipalities involve numerous ways of information and different levels of engagement as we will introduce later on. In earlier works, we argued that the successful introduction of e-participation requires the adaptation of given processes or even the introduction of new processes in the dialogue among citizens and politicians and/or local government officials when introducing online means [33]. Due to the lack of regulatory grounds, the procedures and extent of engaging citizens in on-and offline participatory budgeting offers differ widely.…”
Section: Introductionmentioning
confidence: 99%
“…Municipalities, which intend to introduce e-participation, have difficulties to assess the implications and (financial and human) resources needed to introduce e-participation offers. Since the planning, organization and running of a participatory budget does mean big efforts for a city or municipality, this paper investigates and develops a reference process model for participatory budgeting procedures and therewith extends the reference procedural model (see [33,34]) with particular reference process models for participatory budgeting.…”
Section: Introductionmentioning
confidence: 99%